2015
DOI: 10.1016/j.jff.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro prebiotic activities of tamarillo (Solanum betaceum Cav.) hydrocolloids

Abstract: Available online A B S T R A C TTwo types of hydrocolloids in two distinct zones of red tamarillo (Solanum betaceum Cav.) mesocarp were resistant to digestive enzymes and exhibited different in vitro prebiotic activities. Low molecular weight tamarillo seed mucilage hydrocolloid that was extracted using 1% citric acid or water encouraged the growth of bifidobacteria and lactobacilli more than the high molecular weight tamarillo pulp hydrocolloid that was extracted using 20 mM HEPES buffer or 72% ethanol. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…and Bifidobacterium spp. ), and inhibited the growth of some pathogenic bacteria [218]. In further studies, the seed mucilage hydrocolloids were found to bind bile acids.…”
Section: Solanum Betaceummentioning
confidence: 93%
See 1 more Smart Citation
“…and Bifidobacterium spp. ), and inhibited the growth of some pathogenic bacteria [218]. In further studies, the seed mucilage hydrocolloids were found to bind bile acids.…”
Section: Solanum Betaceummentioning
confidence: 93%
“…Tamarillo is native to the Andes, especially Peru, Ecuador, and Colombia, but is also cultivated in Indonesia, the Philippines, Malaysia, Thailand, Vietnam, and Papua New Guinea [216,217]. There are three main types of tamarillo, which vary in terms of the color of the ripe fruit skin: yellow, red, and purple [218].…”
Section: Solanum Betaceummentioning
confidence: 99%
“…32. (Rycroft, Jones, Gibson and R. a Rastall, 2001), 33 (Gannasin et al, 2015),. 34 (Daou et al, 2014…”
mentioning
confidence: 99%
“…The results of the present study were consistent with those reported by Roberfroid 49 , who noted that, in axenic cultures, most of the microorganisms adapt to use the carbon sources available in the medium. Other studies have evaluated cell growth in mixed cultures 50,51 . The results of the present study highlight the potential of fermenting cactus OLI, such as those of OS, and provide the basis for further investigations on the metabolism of probiotics and its implications.…”
Section: Discussionmentioning
confidence: 99%
“…lactis growth kinetics in the presence of OLI‐A, OLI‐B, OLI‐C and INU were within those reported for different OLI, such as INU, lactulose, fructooligosaccharides and galactooligosaccharides. The decrease in the pH of the medium is an indicator of lactic acid and SCFA production during fermentation.…”
Section: Discussionmentioning
confidence: 99%